Al‐Li Alloy Chemical Milling Waste Solution Synthesis of γ‐AlOOH Bundles for Cr(VI) Rapid Adsorption. Issue 19 (21st May 2020) - Qi, Yuwen; Wei, Lihong; Shi, Dongni; Cai, Wei; Guo, Licun
Abstract: Al‐Li alloy chemical milling waste solution (AlCM) was utilized for the first time to prepare γ‐AlOOH(boehmite) as highly efficient adsorbent for Cr(VI). The NaAlO2 in AlCM reacted with H2 O2 at room temperature for 0.25 h to prepare porous γ‐AlOOH bundles with the specific surface area of 232.2 m 2  g ‐1 . The possible growth mechanism of γ‐AlOOH under CTAB and time was proposed. The kinetics and adsorption properties of Cr(VI) adsorbed by γ‐AlOOH were also investigated. The porous γ‐AlOOH bundles can quickly adsorb Cr(VI) within 20 minutes and show stable recyclability. This study shows that it is a cost‐effective way to treat and recycle AlCM that the γ‐AlOOH is synthesized from AlCM as an adsorbent to remove Cr (VI) heavy metals in wastewater. Abstract : As an adsorbent, porous γ‐AlOOH (boehmite) bundles can removal the Cr(VI) heavy metal from wastewater. Al−Li alloy chemical milling waste solution (AlCM) was utilized for the first time to prepare γ‐AlOOH (boehmite) bundles as a strategy. The kinetics and adsorption properties of Cr(VI) adsorbed by γ‐AlOOH were also investigated. This work demonstrates the feasibility of comprehensive utilization of AlCM to prepare γ‐AlOOH for reducing environmental problems.